A Randomized, Prospective, Split-Face Pilot Study to Evaluate the Safety and Efficacy of 532-nm and 1,064-nm Picosecond-Domain Neodymium:Yttrium-Aluminum-Garnet Lasers Using a Diffractive Optical Element for Non-Ablative Skin Rejuvenation: Clinical and Histological Evaluation - Han, Hye Sung; Hong, Jun Ki; Park, Su Jung; Park, Byung Cheol; Park, Kui Young (Annals of dermatology, 2023)
The advent of fractionated picosecond (ps) lasers has provided an opportunity to explore new ways of creating microinjuries in the skin to induce skin rejuvenation. To compare the efficacy and safety of diffractive optical element (DOE)-assisted ps neodymium: yttrium-aluminum-garnet (Nd:YAG) lasers with 532-nm and 1,064-nm wavelengths (532-nm and 1,064-nm Nd:YAG P-DOE) using a novel fractional handpiece for the treatment of photoaged skin. An guinea pig skin experiment was performed by evaluating the histology of the skin after 532-nm Nd:YAG P-DOE irradiation. A randomized, prospective, split-face study was performed on eight subjects with 532-nm and 1,064-nm Nd:YAG P-DOE. Based on the histological evaluation using guinea pig skin, a reasonable safety profile and the potential to generate effective skin rejuvenation was observed using the 532-nm Nd:YAG P-DOE. Results demonstrated that both 532- and 1,064-nm Nd:YAG P-DOE were similarly effective in improving skin texture and skin pores; however, 532-nm Nd:YAG P-DOE was more effective in treating dyspigmentation. At a preliminary level, this study revealed that 532-nm and 1,064-nm ps Nd:YAG lasers using DOE fractional technology may improve photoaged skin. In conclusion, 532-nm Nd:YAG P-DOE may be especially beneficial for skin with epidermal pigmentary lesions.